MARKOV PROCESSES IN RESEARCHING THE PROBABILITY OF CYBER ATTACKS ON MARINE VESSELS - Zaytseva Тетяна; Kravtsova Людмила; Kaminskaya Наталія (Journal of Information Technologies in Education (ITE), 2023)
Shipping is increasingly relying on digital solutions for everyday tasks. There are constant updates in the field of information technology, data availability, speed of processing and transfer of data with advanced possibilities to optimize work, save costs, increase security and sustainability of business. Along with the growing dependence on automation, the risk of external interference and disruption of key systems significantly increases; hackers can interfere with the operation of the ship or navigation systems, cut off all external communications of the ship or obtain confidential data. Research on cyber security of maritime sector facilities is quite acute today and requires constant attention and improvement. According to cyber security experts in the maritime sector, ground and space equipment systems are most vulnerable to cyberattacks; global positioning systems, electronic cartographic and navigational information systems; flight data registration systems; cargo operations systems; engine, machine and power management systems; access control systems; ship’s public internet networks; administrative systems and networks; communication systems and port infrastructure. Analyzing the above, it can be concluded that the more data is collected, the more accurate reports and response actions to cyber threats will be performed by the ship’s security management system. A careful analysis of the sources of cyberattacks, which occur most often, allows us to assume that this is a random process that obeys the laws that are called Markov processes in the theory of probabilities (or, more precisely, stochastic processes). The subject of the study is the construction of a model based on the properties of Markov processes, which allows for a more detailed study of the process, analysis and forecasting of the development of a cyberincident in order to make a management decision regarding further constructive actions.